The Leadership of Public Bureaucracy in Soppeng - Harbani Pasolong; Aisyah Aisyah; Andi Yahya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The result of the research aimed to described the application of leadership style in public bureaucracy. The method used is the combination of quantitative and qualitative research (triangulation) by using the surfeited sampling of the whole population with 48 people. The result showed that the dominant leadership used in Soppeng is “sarong pawo” where all the decisions or policies were determined by the elite/leader, in this case the leader tends to give instruction to the subordinate. The implementation of sarong pawo influenced by the environment and cronology of the royal traditional culture which adopted the royal culture system into the government system. The internalitation of royal cultural values into the birocraty brings the character that tends to put himself to the higher degree than any other people and also in the relationship hierarchy influenced by the patterns of client patron relationship with the leader. The sorong pawo leadership takes place for 657 years, because no one dare to resist or refuse even they’re right or wrong because the truth as tradition in royal system.